Microfluidic Point-of-Care Testing: Commercial Landscape and Future Directions - Sachdeva, Shivangi; Davis, Ronald W.; Saha, Amit K. (Frontiers in Bioengineering and Biotechnology, 2021)
Point-of-care testing (POCT) allows physicians to detect and diagnose diseases at or near the patient site faster than conventional lab-based testing. The importance of POCT is considerably amplified in the trying times of COVID-19 pandemic. Numerous point-of-care tests and diagnostic devices are available in the market including but not limited to, glucose monitoring, pregnancy and infertility testing, infectious disease testing, cholesterol testing and cardiac markers. Integrating microfluidics in point-of-care testing allows fluid manipulation and detection in a singular device with minimal sample requirements. This review presents an overview of two technologies: (a.) Lateral Flow Assay (LFA) and (b.) Nucleic Acid Amplification upon which a large chunk of microfluidic POCT diagnostics rely on, some of their applications and commercially available products. Apart from this, we also discuss some other microfluidic based microfluidic-based diagnostics dominating the have the major share in the in-vitro diagnostic (IVD) market, current testing landscape for COVID-19 and future prospects of microfluidics in next generation diagnostics.